At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Join our Q&A platform to connect with experts dedicated to providing precise answers to your questions in different areas. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

Solve the equation –15 = –6(3 + x) + 4(x – 6).
X =


Sagot :

Answer:

x=-13.5

Step-by-step explanation:

[tex]-15=-6(3+x)+4(x-6)\\-15=-18-6x+4x-24\\-15=-2x-42\\27=-2x\\x=\frac{-27}{2}[/tex]